Métodos de determinação de evapotranspiração e produtividade de cultivares de trigo irrigado - Fenner, William (2019)
Water availability, fertilizer management and crop rotation are fundamental to the sustainability of agriculture and food security. In this dynamic, the wheat crop has gained space in the Brazilian Midwest region, especially in irrigated crops. The objective of this study was to study the evapotranspiration of wheat in an irrigated system, determined by three methods: FAO, lysimetry and soil water balance. For this, evapotranspiration was estimated and determined using the dual kc methodology, FAO-56, with plants grown in 12 lysimeters filled with soil monoliths, and the loss of water by evaporation measured by weighing small lysimeters. Evapotranspiration was also determined by the water balance method. In this method, the capillary rise and the deep drainage were determined and the hydraulic conductivity equation as a function of time determined by the instantaneous profile method. Soil moisture was determined by a Diviner® 2000 capacitance probe at intervals of 0.10 m to a depth of 0.5 m. The experiment was carried out during two consecutive years, in which BRS 254 varieties were cultivated in 2016 and BRS 394 in the year 2017. The results measured in the lysimeters (standard method) were compared with the data simulated by the dual kc method and determined by soil water balance method, in order to determine the accuracy and efficiency of the methods used. The coefficients used to determine the efficiency of the methods were the RMSE, the RSR and the confidence index "c". The total evapotranspiration of the crop in both years of cultivation was 360 mm, with mean values of 3.87 mm d-1 for cultivar BRS 254- and 4.10-mm d -1 for cultivar BRS 394. The basal coefficients of cultivation in the emergence, tillering, flowering, maturation and harvest stages were 0.42, 0.78, 0.94, 0.74 and 0.47 for cultivar BRS 254 and 0.28, 0.27, 0.65, 0.98 and 0.66 for cultivar BRS 394. The soil water evaporation coefficients at the respective stages are 0.72, 0.52, 0.39, 0.58 and 0.13 for cultivar BRS 254 and 1.04, 0.96, 0.65, 0.34 and 0.51 for cultivar BRS 394. ke represents on average about 47 % of the evapotranspiration of the irrigated wheat crop. The average yield of irrigated wheat of cultivars BRS 254 and BRS 394 ranged from 2.14 to 3.40 and 3.31 to 3.40 Mg ha-1 , respectively, values above the national average for the crop.